Crystal chemistry and physicochemical investigation of aliovalent substituted SnO2 nanoparticles. (February 2021) - Sharma, Deepika; Tripathi, Shalini; Panwar, Ranvir Singh; Dhillon, Gulshan; Bhatia, Anupreet Kaur; Vashisht, Devika; Mehta, S.K.; Kumar, Naveen
Abstract: This paper investigates the physicochemical properties of rare earth metal Dysprosium (Dy) doped SnO2 dilute magnetic semiconducting nanoparticles. Sol-gel method was adopted to synthesize Sn(1-x) Dyx O2 (x = 0, 0.05 and 0.10) compositional series. Structural analysis revealed that all the compositions exhibit pure rutile type tetragonal crystal structure with space group P42 /mnm as manifested by Rietveld refinement without any secondary phases and impurities. FTIR spectra of all the compositions showed a band at 592 cm −1 belonging to Sn–O symmetric vibration. Pure and Dy 3+ modified SnO2 nanoparticles exhibited pseudo-spherical morphology with an average particle size of 16 nm, 19 nm, and 22.8 nm for x = 0, 0.05, and 0.10, respectively as calculated from the statistical bar graph distribution of particles. The particle size increased with increasing Dy 3+ concentration. The enhancement in cell volume with increasing Dy 3+ concentration as calculated from Rietveld refinement studies also complimented TEM results. HRTEM fringe pattern and ring pattern of SAED plot endorsed the formation of tetragonal structure of Sn(1-x) Dyx O2 (x = 0, 0.05 and 0.10) nanoparticles. Photoluminescence spectra of all the compositions displayed a strong emission peak of ~407 nm, which may be ascribed due to oxygen vacancies in the samples. MH hysteresis loop of pure SnO2 showed weak ferromagnetism at low fields and diamagnetic nature at the higher field but Dy 3+ doped SnO2 nanoparticles displayed paramagnetism at x = 0.05 and ferromagnetism at x = 0.10, which might be due to increase in oxygen vacancies upon increasing aliovalent Dy 3+ in the host SnO2 . Highlights: Pure and Dy 3+ doped SnO2 nanoparticles were prepared by the sol-gel method. XRD studies revealed the tetragonal crystal structure for all the samples. PL spectra evidenced the existence of oxygen vacancies in the sample. Diamagnetic to ferromagnetic transition occurred with increasing Dy 3+ concentrations.